Kallikrein-kinin system in human fetoplacental tissues in pregnancy -induced hypertension - Larmie, E.T.; Singh, Harbindar Jeet; Shukri, Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
The pathogenesis·~ of pregnancy-induced ···hypertension·· (Pil-l) remains an enigma. However, it is currently postulated that placental hypoperfusion due to an imbalance of vasoconstrictor and vasodilator substances in the placenta may contribute to the pathogenesis of PIH. Hence, the objectives of this study are: (1) to determine the kininogen {using enzyme immunoassay) and tissue kallikrein levels (using a synthetic chromogenic substrate, S-2266), the substrate and enzyme, respectively, that are responsible for the generation of kinin (a vasodilator); (2) to determine the molecular weight of tissue kallikrein (by Western blot analysis); and (3) to determine the gross effect of fetoplacental tissue extracts on the contraction of rabbit jejunum smooth muscle using various fetoplacental tissues from 12 normotensive pregnant women and 12 women with PIH. No significant differences were found for active, total and inactive tissue kallikrein levels in tissues from both groups. However, kininogen levels and kininogen/total tissue kallikrein ratios were significantly lower in chorion laeve, placental plate chorion, fetal placenta and maternal placenta from women with PIH. The molecular weight of tissue kallikrein was about 52 kDa for both groups. These findings might indicate a lower level of kinin generation in fetoplacental tissues of women with PIH confirming the reported preponderance of vasoconstrictor activity. The higher increase in smooth muscle tone produced by application of the fetoplacental tissue extracts from women with PIH also further supports this postulate.